PHYSICAL FITNESS OF SCHOOLCHILDREN PRACTICAL AND NON-PRACTICAL VOLLEYBALL (Fiep Bulletin - online, 2019)
The objective of this study was to compare anthropometric indicators and the level of physical fitness among non -volleyball practitioners and non - volleyball players. A sample of 32 male students aged 15 to 18 years with mean age of 16.05 ±1.107, regularly enrolled in the private education network of the city of Manaus, were collected. For the evaluation of physicalfitness related to sports performance, anthropometric measurements (weight, height and wingspan) and motor performancetests (sit-and-reach, modified abdominal, horizontal jumping force, vertical jumping force, medicine ball 2kg, agility 4x4, speedrun 30m and run and walk for 12 minutes). Significant difference was found in sit-and-reach tests, modified abdominal, horizontaljumping force, vertical jumping force, medicine ball 2kg pitch, 30m speed run and 12-minute run and walk. It was concluded thatvolleyball schoolchildren obtained better sports performance in all tests, with the exception of the 4x4 agility test, when comparedto non-practicing schoolchildren.